Identifying predictors of university students' mental well-being during the COVID-19 pandemic - Hamzah, Siti Raba’ah; Musa, Siti Nur Syuhada; Badruldin, Muhammad Nur Waafi; Amiludin, Nurul Afifah; Zameram, Qurratul Ain; Kamaruzaman, Muhd Jamil Muhshi; Said, Nur Najwa; Ahmad Hanif, Nursyamimi Amirah (University of South Bohemia in České Budějovice, 2023)
Introduction: Changes caused by the COVID-19 pandemic significantly altered the functioning of different social systems, including the educational one. Closing educational institutions and transferring the educational process to online platforms posed new challenges for students’ academic functioning and well-being in these unexpected circumstances. Aims: This study aimed to explore the role of university students’ academic functioning and personality in predicting their subjective well-being during the online studying implemented in Croatia due to the pandemic caused by the coronavirus. Methods: A sample of 505 university students from different Croatian faculties participated in the online survey, which included their ratings of adjustment to the online learning environment, related difficulties in learning and self-regulation, perception of the online education’s quality, the level of life disruption caused by the pandemic, personality traits, and subjective well-being measures (life satisfaction, positive affect, and negative affect). Results: Results generally revealed that certain aspects of students’ academic functioning during online studying as well as their personality explained a significant proportion of the subjective well-being measures’ variance. Also, the perceived level of life disruption caused by the pandemic and neuroticism were the strongest predictors of students’ subjective well-being, followed by extraversion and conscientiousness. Conclusions: Obtained results indicate that some aspects of academic functioning upon the transition to online studying could contribute to students’ subjective well-being and should be considered when planning interventions to increase their well-being and enhance the quality of the online learning environment in these challenging times.